Strategi Kebertahanan Pedagang Kopi Kaki Lima di Wilayah Rawamangun pada Era Digital: Analisis Berdasarkan Teori Pierre Bourdieu - Ciek Julyati Hisyam; Anggie Natasya Putri; Aninda Rahma Melani; Syifa Rahma Nabila (Journal of Creative Student Research, 2024)
Urban areas are often seen as centers of activity and opportunity, both in economic and social terms. Economic activity in urban areas is a magnet for the wider community and is an inseparable part of everyday human life. The approach used in this research is a qualitative approach with a case study method while the data collection techniques used are observation and in-depth interviews. This research was conducted in May 2024, and is located in the Rawamangun area, East Jakarta. The informants in this study consisted of four street coffee traders who traded in the area. This research understands more about how street vendors as actors in the economic field use strategies in the field to adapt to economic pressures and social changes that occur. Based on Pierre Bourdieu's theory with the concept of arena, street coffee vendors have an arena that does not fully support their business because in the arena there are strict regulations from the authorities and fierce competition with modern coffee entrepreneurs. In addition, in the concept of capital